Identification of synchronized role of transcription factors, genes and enzymes in Arabidopsis thaliana under four Abiotic stress responsive pathways - Mahdi, Rabab (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.